KONSEP DAN MEKANISME PENGAWASAN TERHADAP PERATURAN DAERAH DIHUBUNGKAN DENGAN HAKIKAT OTONOMI DAERAH - Achmad Sodik Sudrajat (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2010)
Surveillance has become an important part of the administration and bureaucracy’s performance which its relation cannot be separated with the public administration management system in the local area. One of the surveillance forms should be doneto the law products that were issued by the local government, particularly Local Regulations (Peraturan Daerah/PERDA). At the moment, the surveillance that could be done to PERDA is through the test performed by the Supreme Court (MA).PERDA that had been appointed should be submitted to the government, through an Academic Text in every PERDA formation. These three concepts are used as the surveillance tools to the local law product (PERDA).